Mass-spectrometric determination of the amino acid sequences in peptides isolated from the protein silk fibroin of Bombyx mori. - Lucas,F; Barber,M; Wolstenholme,WA; Geddes,AJ; Graham,GN; Morris,HR (Biochem J, 1969)
Several peptides were isolated from the protein silk fibroin of Bombyx mori by means of ion-exchange chromatography of a chymotryptic digest. The sequences of three of the peptides, Gly-Ala-Gly-Tyr, Gly-Val-Gly-Tyr and Gly-Ala-Gly-Ala-Gly-Ala-Gly-Tyr, were known from previous chemical work, but the sequence of the fourth, Gly-Ala-Gly-Val-Gly-Ala-Gly-Tyr, was previously only partially known. The necessary volatility for mass-spectrometric examination of the peptides was achieved by permethylation of the N-acetyl-peptide methyl ester derivatives. From the mass spectra it was possible to confirm the known sequences and to establish that of the partially known one. In one instance it was possible to deduce from the same mass spectrum the sequence of a main peptide component and that of a small amount of contaminating peptide. These results demonstrate for the first time the use of mass spectrometry in the determination of the amino acid sequences in peptides from a protein hydrolysate.